Analisis Pragmatik Tindak Tutur Asertif pada Podcast Close The Door Episode “Ayolah Masa Kalian Ga Tau Tujuannya Apa dan Amannya Indonesia!” - Suci Rahmadani; Alber Alber (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to identify the forms, functions, and the most dominant types of assertive speech acts in digital communication. Using a descriptive qualitative approach with content analysis methods, data were collected through observation and note-taking techniques from the Close The Door podcast episode entitled "Ayolah Masa Kalian Ga Tau Tujuannya Apa dan Amannya Indonesia!" ("Come on, Don't You Know What the Goal Is and Indonesia's Security!"). The results found 44 speech data encompassing seven assertive forms: reporting (14 data), stating (12 data), informing (10 data), suggesting (4 data), complaining (3 data), boasting (2 data), and demanding (1 data). The discussion shows that the reporting speech act is highly dominant because the speakers intensively present empirical facts, chronological data, and real field situations to build the validity of arguments related to national stability. The study concludes that assertive speech acts in digital media serve a strategic function to bind the speaker's commitment to truth in order to manage public perception and maintain social harmony.